The Covid Crisis and CEO Pay Balance - Halil D. Kaya; Zahar Rosinsky (SocioEconomic Challenges)
This paper focuses on the socio-economic challenges created by the Covid crisis. More specifically, it examines the impact of the COVID crisis on CEO Pay balance in Nasdaq. The research focuses on the top 10 most valuable firms traded on the NASDAQ. The 2017-2019 period is taken as the pre-Covid period, the 2020-2022 period is taken as the post-Covid period, and the CEO Pay balance is compared across these two periods. For the CEO Pay balance, four variables are used. These are the Pay ratio (which compares the CEO's pay to the average employee’s pay), the CEO/President ratio, the CEO/Top Vice President ratio, and the CEO/Average Vice President ratio. First, the trends in each CEO pay balance variable over the sample period are examined. During the 2017-2022 period, the CEO Pay ratio more than doubled (i.e. a 150% increase), while the CEO/President ratio doubled (i.e. a 100% increase). These findings show that, during this period, the average employee and the President suffered relative to the CEO regarding their pay. When the CEO/Top VP and the CEO/Average VP are examined, the results show little or no difference. Therefore, VPs did well during this period. Non-parametric tests are then performed to compare the pre-Covid and post-Covid periods. The results show that the increase in the CEO pay ratio (i.e. compared to the average worker) was statistically significant. At the same time, the change in the other three variables were insignificant. Finally, regressions are run to see whether there was a significant change in each pay balance variable after COVID-19. After controlling for firm size, growth, leverage, and profitability, there is no significant difference in the CEO pay balance measures pre- versus post-COVID.